Collaborative Business Process Management: Exploring Themes, Achievements, and Perspectives - Niehaves, Björn; Plattfaut, Ralf (18th European Conference on Information Systems, 2010)
Under labels such as global value chains, global production networks, interconnected firms, or outsourcing cross-boundary business processes have gained significant attention in practice and research. However, only little research has yet systematically examined the implications of crossboundary business processes for Business Process Management (BPM). These cross-boundary business processes together with the drivers of collaboration and network management as well as governance form one of the key challenges for today’s BPM research. In this study we thus systematically review literature and seek to answer whether BPM research in Information Systems (IS) has yet embraced and explored the concept of collaboration. We find that collaborative BPM is a growing trend in IS research, but that there still exist significant research gaps. Therefore, we propose a research agenda that points at potentially fruitful directions for future research.